2017
DOI: 10.1002/jid.3317
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking the Household ‘Black Box’: A Gendered Analysis of Smallholder Farmers' Participation in the Cassava (Manihot esculenta crantz) Value Chain in Tanzania

Abstract: Women in developing countries are often omitted from key parts of the agricultural value chains. We used household survey data in bi-probit and ordinary least squares regression models to estimate the determinants of women's participation in cassava cultivation and marketing in Tanzania. Land size and region, among other factors, were significant determinants of household decisions to grow cassava. Policies for improving women's land rights and infrastructure would help to promote their participation in cassav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(40 reference statements)
2
0
1
Order By: Relevance
“…The results presented in this study are consistent with the findings reported by Masamha et al (2018b) in their research on gender analysis of smallholder farmer's participation in the cassava value chain in Tanzania the cassava food value chain. Their study revealed that women had a significant role in the processing stage of the value chain of cassava within households.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results presented in this study are consistent with the findings reported by Masamha et al (2018b) in their research on gender analysis of smallholder farmer's participation in the cassava value chain in Tanzania the cassava food value chain. Their study revealed that women had a significant role in the processing stage of the value chain of cassava within households.…”
Section: Discussionsupporting
confidence: 91%
“…Our study's findings regarding the extent of involvement in the production phase of the cassava value chain by both women and men sharply differ from those of Masamha et al (2018b), as our study showed similar R 2 coefficients for women and men (0.65 and 0.72) in contrast to Masamha et al's results, where the R 2 for females was about twice that of males (0.45 and 0.26). The model's explanation of the overall variation is smaller for men than for women, and the omission of variables like marital status, region, and age, as seen in previous research, may have affected the significance of the outcomes in the OLS model; furthermore, in the male model, the observation regarding the the household head's age aligns with the findings of Ayamga et al (2006), and is statistically significant.…”
Section: The Extent Of Women's Involvement In the Production Phasecontrasting
confidence: 96%
See 1 more Smart Citation